The efficacy and safety of paravertebral block for postoperative analgesia in renal surgery: A systematic review and meta-analysis of randomized controlled trials - Zhao, You; Kan, Yanan; Huang, Xin; Wu, Ming; Luo, Weiping; Nie, Jun (Frontiers in Surgery, 2022)
Background: Paravertebral block (PVB) has been widely used in postoperative analgesia, especially in thoracic and breast surgery. However, the efficacy and safety of PVB for analgesia after renal surgery remains uncertain. Therefore, this study aimed to determine the postoperative analgesic efficacy and safety of PVB in renal surgery. Methods: PubMed, Web of science, Embase and the Cochrane Library databases were systematically searched up to December 20, 2021.All randomized controlled trials (RCTs) evaluating the postoperative analgesic efficacy of PVB in renal surgery were collected. The meta-analysis was performed using RevMan 5.4 and Stata/MP 14.0 software. Results: A total of 16 RCTs involving 907 patients were included in the meta-analysis. 10 studies investigated patients under percutaneous nephrolithotomy (PCNL), and 6 studies were patients under other renal surgery (nephrectomy or pyeloplasty). Compared with control groups (no block, sham block or other nerve blocks), meta-analysis showed that PVB reduced 24-hours postoperative opioid consumption significantly (SMD = -0.99, 95%CI: -1.60~-0.38, P = 0.001, I2 = 92%), and reduced pain scores at various time points within 24 hours at rest and at 1h, 4h, and 24h at movement after renal surgery, furthermore, PVB prolonged the time to first postoperative analgesic requirement (SMD = 2.16, 95%CI: 0.94~3.39, P = 0.005, I2 = 96%) and reduced the incidence of postoperative additional analgesia (OR = 0.14, 95%CI: 0.06~0.33, P < 0.00001, I2 = 50%). Subgroup analysis revealed that the postoperative analgesia effect of PVB was more significant in PCNL, and the use of bupivacaine for PVB seemed to have a better performance. Besides, there was no difference in the incidence of postoperative nausea, vomiting and itching between PVB and control groups. Conclusion: This study indicates that PVB may provide effective postoperative analgesia in patients under renal surgery, especially PCNL patients. Moreover, PVB is a safe analgesic method without significant analgesia related complications.